Concordance between sentinel and subsequent injuries: A prospective study of injured New Zealanders. Issue 2 (February 2019) - Harcombe, Helen; Aldabe, Daniela; Davie, Gabrielle; Wyeth, Emma; Derrett, Sarah
Highlights: Subsequent injuries of the same type, at the same setting or from the same activity occurred frequently in the 24 months following a sentinel injury. 21% of participants had at least one subsequent injury event of the same type as their sentinel injury in 24 months. 26% of participants had at least one subsequent injury event at the same setting as their sentinel injury in 24 months. 17% of participants had at least one subsequent injury involving the same activity as their sentinel injury in 24 months. These findings highlight the potential for injury prevention when injured people present to healthcare providers. Abstract: Objectives: To describe: 1) settings, activities and types of injuries for an 'initial' (sentinel) injury and subsequent injuries over 24 months, and 2) concordance between sentinel and subsequent injury events. Methods: Participants (n = 2856) were recruited to the Prospective Outcomes of Injury Study (POIS) following their sentinel injury event, an injury event resulting in an Accident Compensation Corporation (ACC) entitlement claim. Subsequent injuries were those from additional ACC claims in the following 24 months. Injury settings, activities and types were from electronic ACC claims data. The risks of having a subsequent injury of the same type as the sentinel injury were estimated. Results: Overall, 1653 (58%) participants had 3444 subsequent injury events in 24 months, resulting in 4470 injury diagnoses. Twenty one percent had at least one subsequent injury event of the same type as their sentinel injury; 33% with a spine sprain/strain had at least one subsequent spine sprain/strain. Many participants had at least one subsequent injury event at same setting (26%) as their sentinel injury; of note, 36% of participants whose sentinel injury occurred at home had at least one subsequent injury at home. Seventeen percent of participants had at least one subsequent injury involving the same activity as their sentinel injury; 28% of those whose sentinel injury was a result of contact in sport had at least one subsequent injury also involving sport. Conclusions: Subsequent injuries among people presenting to healthcare providers are common. Greater emphasis should be placed on maximising such healthcare provider contact as an injury prevention opportunity.